Patient, nursing and medical staff experiences and perceptions of the care of people with palliative esophagogastric cancer - Cowley, Alison; Evans, Catrin; Bath-Hextall, Fiona; Cooper, Joanne (Wolters Kluwer, 2016)
Background: Esophagogastric cancer is the fifth most common malignancy and its incidence is increasing. The disease progresses quickly and five-year survival rates are poor. Treatment with palliative intent is provided for the majority of patients but there remains a lack of empirical evidence on the most effective service models to support esophagogastric cancer patients.